MicroRNA: A mediator of diet-induced cardiovascular protection. (October 2021) - Collado, Aida; Jin, Hong; Pernow, John; Zhou, Zhichao
Abstract: Diets containing nutrients such as polyunsaturated fatty acids, polyphenols, or vitamins have been shown to have cardiovascular benefits. Micro (mi)RNAs are fundamental regulators of gene expression and function in the cardiovascular system. Diet-induced cardiovascular benefits are associated with changes in endogenous expression of miRNAs in the cardiovascular system. In addition, emerging studies have shown that miRNAs present in the food can be transported in the circulation to tissues. These exogenous miRNAs may also affect cardiovascular function contributing to the diet-induced benefits. This review discusses the emerging role of both endogenous and exogenous miRNAs as mediators of diet-induced cardiovascular protection. Understanding the mechanisms of diet-mediated actions through modulation of miRNA may provide a potential strategy for new therapies. Highlights: Diets containing nutrients affect endogenous miRNA levels in the cardiovascular system. miRNAs present in diets can be delivered to cardiovascular tissues. Diet-induced benefits may be mediated by the endogenous and exogenous miRNAs.